How did Malaysia Manage its Position as Top 10 World Tourist Destinations in UNWTO Ranking in 2012? - Othman, Nor’Ain; Wee, Hassnah; Hassan, Razip (Journal of Tourism, Sustainability and Well-being, 2014)
There are many reasons contributing to the achievement of Malaysia for being rank as top 10 most visited destinations in the world for the last four years. Among the factors are structures, resources, strategy, policy and leadership. In order to identify how Malaysia manage to be at this rank, a study was carried out on destination branding of Malaysian tourism from destination marketers’ perspectives. The objectives are to identify tourism marketing messages that influence international tourists desire to visit Malaysia and to examine destination marketing agencies attitude towards building “Brand Malaysia” in tourism products. The subject of this research is the most recent promotion involving a new brand entitled “Malaysia Truly Asia” and examines the initiative within the framework of the country’s destination branding and destination image development strategies. An assessment of the part played by destination branding in Malaysian tourism industry at large forms the wider context for the study and conclusions of more general relevance are drawn from the particularities of the case. A quantitative research method is used to examine the attitude of destination marketers towards the awareness on marketing mix used in creating “Brand Malaysia” tourism branding. A total of 300 questionnaires were distributed to travel agencies based on purposive convenient sampling.